Comparison of Rapidly Proliferating, Multipotent Aortic Valve-Derived Stromal Cells and Valve Interstitial Cells in the Human Aortic Valve. (10th September 2019) - Huang, Yuming; Xu, Kang; Zhou, Tingwen; Zhu, Peng; Dong, Nianguo; Shi, Jiawei
Abstract : Aortic valve calcification is a common clinical disease, caused by valve interstitial cells (VICs), which initiate the thickening and then calcification of valve leaflets. Classical valve-derived cells can be seen in different cell populations according to their different morphologies, but it is not clear whether different types of mesenchymal cells exist. In this study, culture conditions for mesenchymal stromal cells were used to selectively isolate valve-derived stromal cells (VDSCs). After subculturing, the morphology, proliferation, multidifferentiation, immunophenotype, and gene expression profiling in isolated VDSCs were compared with those in conventional cultured VICs. VDSCs isolated from human aortic valves were uniform spindle-shaped fibroblasts, had mutilineage differentiation abilities, and proliferated faster than VICs. Classic mesenchymal markers including cluster of differentiation 90 (CD90), CD44, and CD29 were positively expressed. In addition, the stem cell markers CD163, CD133, and CD106 were all expressed in VDSCs. RNA-sequencing identified 1595 differentially expressed genes between VDSCs and VICs of which 301 were upregulated and 1294 were downregulated. Valvular extracellular matrix genes of VDSCs such as collagen type 1, alpha 1 (COL1A1), COL1A2, and fibronectin 1 were abundantly expressed. In addition, runt-related transcription factor 2 and Ki-67 proteins were also markedly upregulated in VDSCs, whereas there was less expression of the focal adhesion genes integrin alpha and laminin alpha in VDSCs compared to VICs. In conclusion, novel rapidly proliferating VDSCs with fibroblast morphology, which were found to express mesenchymal and osteogenic markers, may contribute to aortic valve calcification.